Monogenic lupus - from gene to targeted therapy - Katharina Menzel; Kateryna Novotna; Nivya Jeyakumar; Christine Wolf; Min Ae Lee-Kirsch (SpringerOpen, 2024)
Abstract Systemic lupus erythematosus (SLE) is a prototypic autoimmune disease characterized by loss of tolerance to nuclear antigens. The formation of autoantibodies and the deposition of immune complexes trigger inflammatory tissue damage that can affect any part of the body. In most cases, SLE is a complex disease involving multiple genetic and environmental factors. Despite advances in the treatment of SLE, there is currently no cure for SLE and patients are treated with immunosuppressive drugs with significant side effects. The elucidation of rare monogenic forms of SLE has provided invaluable insights into the molecular mechanisms underlying systemic autoimmunity. Harnessing this knowledge will facilitate the development of more refined and reliable biomarker profiles for diagnosis, therapeutic monitoring, and outcome prediction, and guide the development of novel targeted therapies not only for monogenic lupus, but also for complex SLE.